2006
DOI: 10.1190/1.2194523
|View full text |Cite
|
Sign up to set email alerts
|

Waveform inversion using a logarithmic wavefield

Abstract: Although waveform inversion has been studied extensively since its beginning 20 years ago, applications to seismic field data have been limited, and most of those applications have been for global-seismology-or engineering-seismology-scale problems, not for exploration-scale data. As an alternative to classical waveform inversion, we propose the use of a new, objective function constructed by taking the logarithm of wavefields, allowing consideration of three types of objective function, namely, amplitude only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
185
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(186 citation statements)
references
References 28 publications
1
185
0
Order By: Relevance
“…This causes a fundamental problem of FWI called "cycle-skipping", and results in local minima in the inversion (Shah et al, 2010). Attempts to mitigate this problem include multi-scale inversion (Bunks et al, 1995) and phase unwrap (Shin and Min 2006;Shah et al, 2012). However, these methods only partially solve the problem.…”
Section: Migration Velocity Updatementioning
confidence: 99%
“…This causes a fundamental problem of FWI called "cycle-skipping", and results in local minima in the inversion (Shah et al, 2010). Attempts to mitigate this problem include multi-scale inversion (Bunks et al, 1995) and phase unwrap (Shin and Min 2006;Shah et al, 2012). However, these methods only partially solve the problem.…”
Section: Migration Velocity Updatementioning
confidence: 99%
“…when they are caused by intrinsic attenuation, or by topography), or that are simply too complex to be reconstructed during the first stages of waveform inversion. This approach was also taken for the inversion of the San-Andreas-Fault data (Bleibinhaus et al, 2007), and Shin and Min (2006) have demonstrated for the Rytov approximation that amplitudes are not crucial for waveform inversion. We have done some preliminary tests using true amplitudes, and found that the reconstructions were not as good.…”
Section: Waveform Inversionmentioning
confidence: 99%
“…Recently, the improvements in seismic data acquisition, with large offsets and broad frequency content, as well as the availability of the advanced computational devices, paved the way for FWI to be more practical (Pratt et al, 1996;Shin and Min, 2006;Choi and Alkhalifah, 2013). In fact, FWI still suffers from the high nonlinearity of the objective function, which may result in convergence to local minima (Virieux and Operto, 2009).…”
Section: Introductionmentioning
confidence: 99%